2017
DOI: 10.3390/atmos8020026
|View full text |Cite
|
Sign up to set email alerts
|

Total Lightning Flash Activity Response to Aerosol over China Area

Abstract: Twelve years of measurements of aerosol optical depth (AOD), cloud fraction, cloud top height, ice cloud optical thickness and lightning flash density from 2001 to 2012 have been analyzed to investigate the effect of aerosols on electrical activity over an area of China. The results show that increasing aerosol loading inspires the convective intensity, and then increases the lightning flash density. The spatial distribution of the correlation between aerosol loading and electrical activity shows a remarkable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 54 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…The operation and maintenance of existing high-speed railways and the development of future high-speed railways must face these complex environmental elements. China has a vast territory and different environments in different regions, such as high altitude and strong sandstorms in the west, rain and lightning in the south, typhoons in the southeast, and severe cold in the northeast [18][19][20][21], as shown in Fig. 3.…”
Section: Introductionmentioning
confidence: 99%
“…The operation and maintenance of existing high-speed railways and the development of future high-speed railways must face these complex environmental elements. China has a vast territory and different environments in different regions, such as high altitude and strong sandstorms in the west, rain and lightning in the south, typhoons in the southeast, and severe cold in the northeast [18][19][20][21], as shown in Fig. 3.…”
Section: Introductionmentioning
confidence: 99%
“…Lightning and its intensity are governed by the form of moist convection, which is controlled by dynamics/thermodynamics, including the roles of aerosols [1][2][3][4][5][6][7][8][9]. Several studies were conducted to understand the impact of aerosols on lightning [10][11][12][13][14][15]. The reduced droplet size in the presence of a high aerosol concentration [16][17][18][19] suppresses the collision and coalescence processes of droplets into raindrops, which eventually inhibits the warm rain process [20].…”
Section: Introductionmentioning
confidence: 99%
“…When verifying the effect of aerosols on electrical activity over China, Zhao et al [47] concluded that an increase in aerosol loading delayed the formation of warm cloud rain and increased convection intensity due to the cloud droplet size, where many smaller droplets were transported to the freezing region by currents within the cloud, forming more ice particles and more hail. The particles participated in the electrification process, resulting in storms with intense electrical activity.…”
Section: Introductionmentioning
confidence: 99%